1980
DOI: 10.1038/283157a0
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variance of laboratory outbred Swiss mice

Abstract: The extent of allelic variation has been estimated at 46 structural gene loci within three major colonies of Swiss mice and between inbred derivative strains. The colonies have retained nearly the same amount and type of variation found in natural murine or human populations despite laboratory propagation for more than 50 years (175 generations). The population genetic structures of the Swiss mouse colonies were comparable to an island population in which random fixation, and not inbreeding or population bottl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
100
0
3

Year Published

1981
1981
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 152 publications
(107 citation statements)
references
References 29 publications
4
100
0
3
Order By: Relevance
“…As described in detail in Swallow et al (1998a), outbred, genetically variable Rice and O'Brien, 1980) laboratory house mice of the Hsd:ICR strain were purchased from Harlan Sprague Dawley in 1993. After two generations of random mating, mice were randomly paired and assigned to 8 closed lines (10 pairs in each).…”
Section: Animalsmentioning
confidence: 99%
“…As described in detail in Swallow et al (1998a), outbred, genetically variable Rice and O'Brien, 1980) laboratory house mice of the Hsd:ICR strain were purchased from Harlan Sprague Dawley in 1993. After two generations of random mating, mice were randomly paired and assigned to 8 closed lines (10 pairs in each).…”
Section: Animalsmentioning
confidence: 99%
“…Estimates of genetic variation in this line have indicated that despite over 50 years of breeding they are very similar to wild mouse populations (Rice & O'Brien, 1980 with young adulthood. The mice were housed individually in clear shoebox cages in a temperature and humidity controlled colony room and were maintained on a 12 h light/dark cycle.…”
Section: Subjectsmentioning
confidence: 99%
“…These mice are an outbred strain that was derived in 1926 from an original colony of non-inbred Swiss mice consisting of 2 males and 6 females. Estimates of genetic variation in this line have indicated that despite over 50 years of breeding they are very similar to wild mouse populations (Rice & O'Brien, 1980). For this study, 241 male, CD-1 mice were obtained from Harlan Sprague Dawley (Indianapolis, IN).…”
Section: Subjectsmentioning
confidence: 99%
“…Mice and sample collection Barrier maintained Hsd:athymic nude-nu (Pantelouris 1968) and outbred Hsd:ICR (CD-1) (Rice & O'Brien 1980) mice were purchased from Harlan, Italy (S. Pietro al Natisone, Italy). CB6F1/J (BALB/cJ 3 C57BL/6J) hybrid mice were supplied by a CNR-IBC barrier facility (Monterotondo Scalo, Italy) and shipped in protective, ltered boxes, transported by climatecontrolled van and acclimatized for at least 3 days in the vivarium prior to use.…”
Section: Methodsmentioning
confidence: 99%